Relationship between conventional and Islamic interbank rates of a dual banking system in Malaysia, Middle East, and Western countries / Zetty Zahureen Mohd Yusoff and Nur Lylia Azha - Mohd Yusoff, Zetty Zahureen; Azha, Nur Lylia (Universiti Teknologi Mara, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2019)
The purpose of this research is to investigate the relationship between conventional monetary policy rate (CIMMR) and Islamic monetary policy rate (IIMMR) in Malaysia and selected Middle East countries and Western countries. This study runs a panel Cointegration test, a panel VECM and Wald test to examine the relationship and causal effect between the CIMMR and IIMMR for the sample of six countries starting from 2009 until 2018 based on monthly and yearly basis dataset. This study finds that CIMMR and IIMMR, in monthly and yearly basis, are both cointegrated and have a long-run relationship amongst them. Our findings confirm that there is a long run causality effect between conventional and Islamic monetary policies based on monthly interbank rates. Our findings further confirm that there is a short run causality effect between conventional and Islamic monetary policies based on yearly interbank rates. We confident that the implication of Islamic interbank rates in the implementation of monetary policy within a dual system is very high as proven by taking into consideration a different regions as samples for this panel study. To the best of the authors' knowledge, this would greatly contribute to the body of knowledge in the field of monetary policy.